The search for a unifying diagnosis involving neurological, endocrine and immune dysfunction: a case report of a novel presentation of DAVID syndrome - M. Price; P. L. Hofman; K. Hsiao; H. F. Jones (BMC, 2022)
Abstract Background We report a novel presentation of deficit in anterior pituitary function with variable immune deficiency (DAVID) syndrome in a healthy young girl presenting in Addisonian crisis with raised intracranial pressure. Nearly all cases of DAVID syndrome described in the literature have presented with recurrent infections and variable immunodeficiency. Pseudotumour cerebri has not been reported in DAVID syndrome to date. Case presentation A four-year-old girl represented to hospital with vomiting, confusion and diplopia after ten days of tiredness, neck and abdominal pain, and headache. Her cranial nerve examination demonstrated a right abducens nerve palsy and papilloedema, and she was found to have ketotic hypoglycaemia and hypocortisolaemia secondary to adrenocorticotrophic hormone (ACTH) deficiency. Her neuroimaging was consistent with pseudotumour cerebri, and her lumbar puncture opening pressure confirmed raised intracranial pressure (30-40 cmH2O). Cerebrospinal fluid analysis was normal. The patient's symptoms improved with hydrocortisone replacement and acetazolamide, but the raised intracranial pressure recurred after acetazolamide was discontinued. She was subsequently found to have panhypogammaglobulinaemia, and DAVID syndrome was diagnosed. Genetic testing demonstrated a truncating mutation in the NFKB2 gene c.2557C > T, p.(Arg853*). Conclusions This case demonstrates pseudotumour cerebri as a novel neurological presentation of DAVID syndrome, highlights the rare association between adrenal insufficiency and intracranial hypertension, and shows the challenges in diagnosing isolated ACTH deficiency. We emphasise that cortisol should be checked in pre-pubertal children with pseudotumour cerebri and a diagnosis of DAVID syndrome considered in those presenting with low cortisol and neurological symptoms.